Vibrant Architecture. Matter as a CoDesigner of Living Structures (2015)
The cosmos is composed of many different species of stardust (Sagan, 2007) and despite our advanced, secular knowledge, we imagine these primordial substances give rise to a universe, fashioned in our own image, in which Nature and the technological expressions of the human mind, are cleaved. This chapter proposes that the material agency within vibrant matter is a real, physical phenomenon and ultimately a testable proposal, which is based on a new set of ideas about reality that paint a portrait of our universe. This is far more autonomous, lively and sensitive than the one that has historically framed western discourses that have relied on human reason for instruction. The lively character of vibrant matter is examined within this context and its agency attributed to real fundamental forces, grounded in quantum physics, rather than being the product of vitalistic theories (Bergson, 1922, p.44; Driesch, 1914, p.vi; Spuybroek, 2011; Bennett, 2010, pp.83–84), or psychological responses to material groupings (Bennett, 2010, p.4). My research seeks to empower matter by recognizing that its innate vitality resides within molecular bonds, which forge assemblages that can interact with and respond to their surroundings. Locating the liveliness of vibrant matter within the material realm provides the basis for an experimentally testable set of observations that may enable its better characterization and identify possible applications in architectural design.